Pengaruh Kualitas Produk dan Kualitas Pelayanan Terhadap EWOM dan Keputusan Pembelian di Restaurant Haraku Ramen Grand Indonesia - Vanessa Anastashia; Rivera Pantro Sukma (Indonesian Journal Publisher, 2025)
This study aims to examine the influence of product quality and service quality on electronic word of mouth (eWOM) and purchase decisions at Haraku Ramen Restaurant, Grand Indonesia. Employing a quantitative approach, data were collected through a questionnaire distributed to 150 respondents and analyzed using SmartPLS version 3 to assess the relationships among variables. The findings indicate that service quality has a significant positive impact on purchase decisions but does not significantly influence eWOM. This suggests that although good service enhances consumer satisfaction, it does not necessarily motivate customers to share their experiences online. Conversely, product quality does not significantly affect purchase decisions but has a positive effect on eWOM, as customers tend to share favorable reviews when the food meets or exceeds expectations. Furthermore, eWOM has a significant positive influence on purchase decisions, where positive online reviews enhance consumer trust and encourage new customers to try the product. These results highlight the differentiated roles of product and service quality in shaping consumer behavior—service quality drives immediate purchasing actions, while product quality contributes more substantially to the restaurant’s online reputation through eWOM. The study underscores the strategic importance of managing both aspects to optimize customer engagement and decision-making.